Factors Affecting Women of Age Fertile in Choosing Injectable Contraceptives in the Village of Bangun Rejo Kec. Tanjung Morawa Deli Serdang Regency In 2022 - Ribur Sinaga (Institute of Computer Science (IOCS), 2022)
The factors that influence women of childbearing age to choose injectable contraceptives are: Knowledge, education, socioeconomic, age and family support factors. Knowledge is a result of curiosity through sensory processes, especially in the eyes and ears towards certain objects. Knowledge is an important domain in the formation of open behavior donsu Family planning (KB) is a way to prevent pregnancy through hormonal injections. The advantages of injection contraception are very effective, long-term pregnancy prevention, does not affect husband and wife relationships, does not contain estrogen so that it does not have a serious impact on heart disease and blood clotting disorders, does not have an effect on exclusive breastfeeding (ASI), and has few side effects. While the side effects of using injection contraceptive are menstrual cycle disorders, vaginal discharge, acne, increased body weight, nausea, vomiting, dizziness and hair loss. The research method used in this study was descriptive analytic with a cross sectional approach. The main informant in this study was the injection family planning acceptor. This research was conducted at in The Village Of Bangun Rejo Kec. Tanjung Morawa Deli Serdang Regency In 2022 from April to June 2022. The results showed that there was a significant relationship between Knowledge, Education, Socio-economic, Age and Family Support on the choice of injection contraceptives. For further researchers, it is necessary to do further on the variables of ethnicity and occupation using analytical methods and qualitative research methods. Keywords: Injectable Contraceptives, Fertile Age Women, Factors